Gender Justice in Islamic Inheritance Law: A Comparative Study of Turkey and Tunisia - Husnayain, Nilna; Syuroya, Khofifah Indah Imas (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
Islamic inheritance law has long beena subject of debatewithindiscussionsof gender equality, particularlyconcerningthe rule that men receive twice the share of women. This debate takesvariousforms across Muslim countries, notably in Turkey and Tunisia. This article examines how both countries address the tension between maintaining Islamic inheritance rules and adapting them to demands for equality. The study aims to compare Turkey’s adoption of Western civil law with Tunisia’s retention of Islamic law whileallowingspace for reform. The research method employed is a literaturereviewwith a juridical-comparative approach. The findings show that Turkey emphasizes egalitarianismthrough the adoption ofcivillaw,while Tunisia develops progressive discourse within the Islamic framework. The comparison reveals that gender equality issues in inheritance law are not solely rooted in normative texts but are also shapedby thepolitical, social, and cultural dynamicsofeachcountry.